1992
DOI: 10.1111/j.1365-2125.1992.tb04134.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selective serotonin re‐uptake inhibitors on cytochrome P4502D6 (CYP2D6) activity in human liver microsomes.

Abstract: inhibited CYP2D6 activity. The major circulating metabolites of paroxetine in man produced negligible inhibition. In contrast, norfluoxetine the active metabolite of fluoxetine, was a potent CYP2D6 inhibitor (0.43 piM). CYP2D6 activity was also diminished by the tricyclic antidepressant drugs clomipramine (2.2 pM), desipramine (2.3 pRM) and amitriptyline (4.0 IIM). These findings suggest that compounds with SSRI activity are likely to interact with human CYP2D6 in vivo with the potential of causing drug intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
164
2
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(176 citation statements)
references
References 12 publications
8
164
2
2
Order By: Relevance
“…As a result, these women may take selective serotonin reuptake inhibitors (SSRIs) to ameliorate hot flashes but there are potential pharmacological consequences to this strategy. Some of the SSRIs are metabolitically altered by the CYP2D6 enzyme product [39]. It is therefore possible to envision a drug interaction whereby SSRIs block the metabolic activation of tamoxifen.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, these women may take selective serotonin reuptake inhibitors (SSRIs) to ameliorate hot flashes but there are potential pharmacological consequences to this strategy. Some of the SSRIs are metabolitically altered by the CYP2D6 enzyme product [39]. It is therefore possible to envision a drug interaction whereby SSRIs block the metabolic activation of tamoxifen.…”
Section: Tamoxifen the First Sermmentioning
confidence: 99%
“…The SSRIs are twice as effective as the "placebo" effect at reducing menopausal symptoms in randomized clinical trials [138][139][140], so there is naturally an increased usage of SSRIs with long-term tamoxifen treatment to maintain compliance. Unfortunately, the metabolism of tamoxifen to hydroxylated metabolites [141][142][143] and the metabolism of SSRIs [39,[144][145][146][147] both occur via the CYP2D6 gene product. Indeed Stearns and coworkers [97] showed that the SSRI inhibitor paroxetine reduced the levels of endoxifen during adjuvant tamoxifen therapy and endoxifen levels decrease by 64% in women with wild type CYP2D6 enzyme.…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%
“…This removal of the carbon at the methylenedioxy position is catalyzed by cytochrome P4502D6 (CYP2D6) (Bloomer et al, 1992;Crewe et al, 1992), yielding a catechol that is subsequently both methylated and conjugated (Tulloch and Johnson, 1992). The metabolites of paroxetine are considered to be pharmacologically inactive (Kaye et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…SSRIs such as fluoxetine [3], paroxetine [4] and sertraline [5] are extensively metabolized by the liver, whereas citalopram is partially eliminated unchanged by the kidneys [1,6]. Although the enzyme(s) responsible for the metabolism of SSRIs has not yet been fully characterized, in vitro human liver microsomal studies have suggested that an isoform of cytochrome P450, CYP2D6, is involved in the metabolism of SSRIs [7][8][9], being in agreement with an in vivo human panel study [10].…”
Section: Introductionmentioning
confidence: 99%